Biochemical characterization of the minimal domains of an iterative eukaryotic polyketide synthase - Sabatini, Martín (2018)
Iterative type I polyketide synthases (PKS) are megaenzymes essential to the biosynthesis of an enormously diverse array of bioactive natural products. Each PKS contains minimally three functional domains, β-ketosynthase (KS), acyltransferase (AT), and acyl carrier protein (ACP), and a subset of reducing domains such as ketoreductase (KR), dehydratase (DH), and enoylreductase (ER). The substrate selection, condensation reactions, and β-keto processing of the polyketide growing chain are highly controlled in a programmed manner. However, the structural features and mechanistic rules that orchestrate the iterative cycles, processing domains functionality, and chain termination in this kind of megaenzymes are often poorly understood. Here, we present a biochemical and functional characterization of the KS and the AT domains of a PKS from the mallard duck Anas platyrhynchos (ApPKS). ApPKS belongs to an animal PKS family phylogenetically more related to bacterial PKS than to metazoan fatty acid synthases. Through the dissection of the ApPKS enzyme into mono- to didomain fragments and its reconstitution in vitro, we determined its substrate specificity toward different starters and extender units. ApPKS AT domain can effectively transfer acetyl-CoA and malonyl-CoA to the ApPKS ACP stand-alone domain. Furthermore, the KS and KR domains, in the presence of Escherichia coli ACP, acetyl-CoA, and malonyl-CoA, showed the ability to catalyze the chain elongation and the β-keto reduction steps necessary to yield a 3-hydroxybutyryl-ACP derivate. These results provide new insights into the catalytic efficiency and specificity of this uncharacterized family of PKSs.